2022
DOI: 10.1186/s12889-022-12850-5
|View full text |Cite
|
Sign up to set email alerts
|

The physical and mental health of Australian truck drivers: a national cross-sectional study

Abstract: Background The negative health consequences of truck driving are well documented. However, despite the distinct occupational challenges between long- and short-haul driving, limited research has been conducted on how the health profile of these drivers differ. The aims of this study were to characterise the physical and mental health of Australian truck drivers overall, and to identify any differences in factors influencing the health profile of long-haul compared to short-haul drivers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Findings from this study of women truck drivers are consistent with those of other authors who concluded that although truck drivers experience isolation (Johnson et al, 2021) and mental health issues (Crizzle et al, 2020; Shattell et al, 2010; van Vreden et al, 2022), they may not seek professional help for assistance with these problems. In this particular sample, a majority of participants had health insurance.…”
Section: Discussionsupporting
confidence: 91%
“…Findings from this study of women truck drivers are consistent with those of other authors who concluded that although truck drivers experience isolation (Johnson et al, 2021) and mental health issues (Crizzle et al, 2020; Shattell et al, 2010; van Vreden et al, 2022), they may not seek professional help for assistance with these problems. In this particular sample, a majority of participants had health insurance.…”
Section: Discussionsupporting
confidence: 91%
“…We also know that truck drivers tend to downplay their health risks and that there are environmental and attitudinal barriers preventing them from following through with their intentions to make lifestyle changes [ 22 , 57 ]. Previous literature has also highlighted that the risk factor sub-themes identified in this study can lead to varied medical conditions, increased crashes, and poor mental health and need to be mitigated where possible [ 4 , 28 , 54 ]. These risks are also echoed across other occupational groups and pose ongoing challenges for creating effective interventions to reduce years of time lost, lost productivity and future health costs for treating mental ill-health [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys conducted with Australian truck drivers as part of the Driving Health Project [ 26 – 28 ] have shown that additional domains beyond occupational factors, (i.e., lifestyle and personal factors), do indeed influence driver physical and mental health, however, we are unsure of the impact of these factors from the driver’s perspective and this study contributes to this body of knowledge.…”
Section: Introductionmentioning
confidence: 96%
“…The China Statistical Yearbook showed that the total number of traffic accidents in 2020 was 2,44, 674, with 61,703 people killed, 2,50,723 injured, and 1.31 billion RMB in direct property losses. In recent years, studies on the prevalence of psychological symptoms and associated correlators in motor vehicle drivers received some coverage ( 4 , 5 ). For example, it is reported that occupational strain, neuroticism, and psychological symptoms are all positively correlated in metro drivers ( 6 ).…”
Section: Introductionmentioning
confidence: 99%